Penerapan Aksara Lontaraq Pada Karya Keramik Dekoratif Di Agung Grazinia Keramik - Sri Devita; Ni Kadek Karuni; Ida Ayu Artayani (Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
The Lontaraq script is a cultural heritage from the Bugis tribe that must be preserved. Therefore, the creator adopted the concept of the Lontaraq script which was applied to decorative ceramic works. The ceramic works created became an identity for the Bugis-Makassar tribe which is related to history. 1) Exploration, 2) Design 3) Embodiment, can be seen the result of creation in the form of a work. The work is designed and created through an independent project study program at CV. Agung Grazinia ceramics, a company engaged in the ceramics industry, a company that produces its own dyes, besides that it also concentrates on producing ceramic motifs Bali.